High Precision Implementation With Design Considerations and Experimental Tracking Results for Single-Sensor Optical Communication Terminal - Yunjie Teng; Min Zhang; Shoufeng Tong (IEEE Photonics Journal, 2019)
Vibration interference reduces the precision of control system and leads to the instability of the satellite optical communication link. So how to improve the tracking accuracy of terminal system under vibration conditions is an important work for the laser communication systems. In this paper, an experiment was conducted to investigate the high precision tracking system with single-sensor consideration, which can be accomplished with a servo control system combined with the coarse and fine tracking technologies, the tracking data analysis has been presented to estimate the performance based on reasonably tested which consists of three cases collected including different vibration amplitude and acceleration settings. The high tracking precision implementation are carried out on a servo control experiment, and the obtained test results (less than 2 μrad) demonstrate the effectiveness of the proposed single-sensor and multiple-axis tracking scheme.